Impact of Sarcopenia on Simultaneous Pancreas and Kidney Transplantation Outcomes: A Retrospective Observational Cohort Study. Issue 10 (October 2020) - Meier, Raphael P.H.; Noguchi, Hiroshi; Kelly, Yvonne M.; Sarwal, Minnie; Conti, Giulia; Ward, Casey; Halleluyan, Ran; Tavakol, Mehdi; Stock, Peter G.; Freise, Chris E.
Abstract : Background: Sarcopenia has been identified as a predictive variable for surgical outcomes. We hypothesized that sarcopenia could be a key measure to identify frail patients and potentially predict poorer outcomes among recipients of simultaneous pancreas and kidney (SPK) transplants. Methods: We estimated sarcopenia by measuring psoas muscle mass index (PMI). PMI was assessed on perioperative computed tomography (CT) scans of SPK recipients. Results: Of the 141 patients identified between 2010 and 2018, 107 had a CT scan available and were included in the study. The median follow-up was 4 years (range, 0.5–9.1 y). Twenty-three patients had a low PMI, and 84 patients had a normal PMI. Patient characteristics were similar between the 2 groups except for body mass index, which was significantly lower in low PMI group ( P < 0.001). Patient and kidney graft survival were not statistically different between groups ( P = 0.851 and P = 0.357, respectively). A multivariate Cox regression analysis showed that patients with a low PMI were 5 times more likely to lose their pancreas allograft (hazard ratios, 5.4; 95% confidence intervals, 1.4-20.8; P = 0.015). Three out of 6 patients lost their pancreas graft due to rejection in the low PMI group, compared with 1 out of 9 patients in the normal PMI group. Among low PMI patients who had a follow-up CT scan, 62.5% (5/8) of those with a functional pancreas graft either improved or resolved sarcopenia, whereas 75.0% (3/4) of those who lost their pancreas graft continued to lose muscle mass. Conclusion: Sarcopenia could represent one of the predictors of pancreas graft failure and should be evaluated and potentially optimized in SPK recipients. Abstract : Supplemental Digital Content is available in the text.